KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V - Ardiansah, Wilda Alfian; Lingga Nico Pradana; Naniek Kusumawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Student thinking skills are student test scores after completing a lesson or problem. This research aims to find out whether the use of the PBL model assisted by learning media is effective on the thinking skills of fifth grade elementary school students. The subjects in this research were students of classes V A and V B at SDN 02 Mojorejo, Madiun City. The type of approach to research is quantitative with a quasi experimental design type of research that uses a control group pretest-posttest design. The sampling technique used a saturated sampling technique, the sample in this study was 56 students divided into two classes. At SDN 02 Mojorejo class V A as an experimental class was given treatment using the PBL model and at class V B as a Kontron class was given treatment using direct learning. The instrument used for data collection was providing pretest and posttest questions. The technique used for data processing is to carry out normality and homogeneity tests, then continue with the independent sample T test. The results of the research obtained a p-value < 0.05, namely 0.00 < 0.05 so that H1 was accepted and H0 was rejected. So there is an influence of the PBL model assisted by learning media on the thinking skills of fifth grade elementary school students.